Accountability For Corruption Of Village Funds By The Head Of Paridanggaran Village Toba Samosir Regency (Study Verdict Number: 55 / Pid.Sus-TPK/2018 / FR.Mdn) - Panjaitan, Uli; Kusbianto, Kusbianto; Simamora, Melki Suhery (Universitas Dharmawangsa, 2025)
Cases of abuse that occur in village fund management are carried out with various modus operandi such as drafting a budget above the market price and then paying based on other agreements, borrowing while the village fund by moving funds to a personal account and then not being returned. The formulation of the problem is how the village fund deviation by The Village Head of Paridanggaran, Toba Samosir regency, North Sumatra Province, how the accountability of perpetrators of village fund corruption in the decision of PN. Tipikor Number : 55 / Pid.Sus-TPK/2018 / FR.Mdn, how the basis of consideration of the judge handed down the verdict against the defendant in the decision of PN. Tipikor Number: 55 / Pid.Sus-TPK/2018 / FR.Mdn. The research method used is descriptive analysis that leads to normative juridical law research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary Data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the deviation of village funds by the head of Pardinggaran Village related to village funds in 2016 Toba Samosir regency, North Sumatra province is the village fund budget that has been disbursed by the defendant Marhuarar Pangaribuan as the head of Pardinggaran village, but in carrying out activities using village funds not included other village officials, should be used to finance activities in accordance with the draft Paridanggaran village budget. Accountability perpetrators of corruption in the village Fund decision PN. Tipikor Number: 55 / Pid.Sus-TPK/2018 / FR.Mdn is Marhuarar Pangaribuan sentenced to prison for 2 years 6 months and a fine of Rp.50.000.000, - (fifty million rupiah).